Pengatur Suhu Paraffin Bath Menggunakan Android Berbasis Arduino - TW Wisjhnuadji; Arsanto Narendro; Mohammad Ilham (Ikatan Ahli Informatika Indonesia, 2018)
Paraffin bath is one method of physiotherapy that utilizes hot media, Here peulis make paraffin bath tool that can heat with medianya in the form of wax therapy on this tool can be accessed through android so user can monitor temperature dikala tool left behind. At the time of heating the temperature will reach - + 100 ° C to dilute Paraffin wax contained in the container (container), the temperature setting limits used for therapy is the temperature between 47 ° C to 57 ° C. Hot therapy is carried out using paraffin that has been liquid and at a stable temperature. Temperature of lillin can be set through android according to user or patient needs (user), Therapy process done as much as 8-10 times by dipping body part (hand, foot, etc) that want to therapy into container (container) containing candle which is ready to be used for therapy if the part that can not get into the container can use a brush in a way applied to the affordable part as much as 8-10 times evenly. In the design of this module is divided into two parts, namely the design of hardware and software. The hardware of this tool consists of Microcontroller, power supply circuit, driver heater circuit, Bluetooth circuit, relay circuit and infrared. The software is designed using Arduino IDE c language to provide instructions on ATMega328 Microcontroller (Arduino Uno R3) to operate the tool working system.